Labeling of cancer cells with magnetic nanoparticles for magnetic resonance imaging. Issue 5 (28th June 2013) - Weis, Christian; Blank, Fabian; West, Adrian; Black, Gregory; Woodward, Robert C.; Carroll, Matthew R.J.; Mainka, Astrid; Kartmann, René; Brandl, Andreas; Bruns, Heiko; Hallam, Elizabeth; Shaw, Jeremy; et al.
<x xml:space="preserve">Abstract</x> Purpose The process of invasion and metastasis formation of tumor cells can be studied by following the migration of labeled cells over prolonged time periods. This report investigates the applicability of iron oxide nanoparticles as a magnetic resonance imaging (MRI) contrast agent for cell labeling. Methods γFe2O3 nanoparticles prepared with direct flame spray pyrolysis are biofunctionalized with poly‐l‐lysine (PLL). The nanoparticles within the cells were observed with transmission electron microscopy, bright‐field microscopy, and magnetorelaxometry. MRI of labeled cells suspended in agarose was used to estimate the detection limit. Results PLL‐coated particles are readily taken up, stored in intracellular clusters, and gradually degraded by the cells. During cell division, the nanoparticle clusters are divided and split between daughter cells. The MRI detection limit was found to be 25 cells/mm3 for R2*, and 70 cells/mm3 for R2. The iron specificity, however, was higher for R2 images. Due to the degradation of intracellular γFe2O3 to paramagnetic iron ions within 13 days, the R1, R2, and R2* contrast gradually decreased over this time period to approximately 50% of its initial value. Conclusions These results suggest that PLL‐coated γFe2O3 nanoparticles can be used as an MRI contrast agent for long‐term studies of cell migration. Magn Reson Med 71:1896–1905, 2014. © 2013 Wiley Periodicals, Inc.